Identificación y caracterización de la infección activa por citomegalovirus en recién nacidos prematuros - González Ramírez, Javier (Universidad Autónoma Metropolitana, 2013)
Background: The cytomeglovirus infection is among the most feared complications in patients with immunological immaturity (preterm) and immunosuppressed (patients with bone marrow transplantation). The antigenemia or the polymerase chain reaction (PCR) tests have been routinely used for the detection of CMV in immunosuppressed patients. However, using these techniques for the diagnosis of active CMV infection in preterm infants has been limited because the vascular access is difficult. For this reason, it has turned to alternative samples such as blood collection in filter paper cards (Guthrie card). Furthermore, it has been proposed that the characterization of the surface proteins, such as gB is necessary because, apparently the presence of a particular genotype and the presence of genotype mixtures, in the same patient can affect the development of the syndrome caused by CMV. Objective: The aim of this work was to identify and characterize active CMV infection in preterm patients and pediatric patients with bone marrow transplantation. Methods: It was evaluated 271 samples of saliva and 2171 preserved blood in Guthrie cards of preterm infants (RNP) obtained from the Hospital de la Mujer of Mexico City. Real time PCR (PCR-TR) and n-PCR was performed in DNA extracted from Guthrie cards, besides of n-PCR of saliva, and as a gold standard infection with CMV in cell culture. It was used also a nested multiplex PCR to determine the distribution of CMV genotypes in 30 mexican patients who underwent bone marrow transplantation from the Hospital Infantil de México Federico Gómez and Centro Médico Nacional La Raza, IMSS from Mexico City. Results: We evaluated 271 blood samples from Guthrie cards and 271 saliva samples for the presence of CMV. Only 3.69% were positive in culture of saliva, 4.05% were positive by n-PCR in Guthrie cards, 4.05% were positive by RT-PCR in Guthrie cards and 1.10% were positive by n-PCR in saliva. The sensitivity (S) of n-PCR and RT-PCR on Guthrie Cards were 100%, specificity (E) 99%, positive predictive value (PPV) of 90% and negative predictive value (NPV) 100%. The results in n-PCR in saliva were: S of 30%, E 99%, PPV 75% and NPV 97%. Congenital infection with CMV in RNP does not represent a risk to the RNP as none of the RNP detected with congenital CMV infection presented symptoms; the presence of infection in these RNP did not influence their anthropometric characteristics and initial evaluation. The genotypes found in the patients with bone marrow transplantation were: gB1, 9/30 (30%); gB2, 8/30 (27%); gB3, 4/30 (13%), y gB4, 1/30 (3%); mixed genotypes were found in 8/30 patients (27%). Conclusions: The sensitivity in PCR or RT-PCR Guthrie cards was 100%. No relationship was found between viral load and symptoms since no subject had symptomatic infection. The predominant genotypes in our population were gB2 and GB1. It was found a high proportion of mixed genotypes.; La infección por Citomegalovirus (CMV) es una de las patologías de mayor riesgo en los pacientes con inmadurez inmunológica (recién nacidos prematuros) e inmunosuprimidos (pacientes con trasplante de médula ósea). La glicoproteína B de superficie (gB), y la presencia de uno o más genotipos, puede influir en el desarrollo de la enfermedad. La antigenemia o reacción en cadena de la polimerasa (PCR) a partir de sangre, se ha usado rutinariamente para la detección de CMV en pacientes inmunosuprimidos. El uso de estas técnicas para diagnosticar CMV en recién nacidos prematuros ha sido limitado debido al difícil acceso vascular. El empleo de sangre absorbida en tarjetas de papel filtro (tarjeta de Guthrie) es una buena alternativa por la cantidad de muestra que se utiliza. Objetivo: Identificar y caracterizar la infección activa por CMV en pacientes recién nacidos prematuros y pacientes pediátricos con trasplante de medula ósea. Material y Métodos: Se tomaron 271 muestras de saliva y 271 de sangre conservadas en tarjetas Guthrie, de 271 recién nacidos prematuros del Hospital de la Mujer, en la Ciudad de México D.F. Se realizó n-PCR y PCR en tiempo real (PCRTR) en ADN extraído de tarjetas Guthrie, además de n-PCR de saliva, y como estándar de oro, infección en cultivos celulares para detección de CMV. Se utilizó un PCR multiplex anidado para determinar los genotipos de la glicoproteína de CMV gB en 30 pacientes pediátricos mexicanos con trasplante de médula ósea del Hospital Infantil de México Federico Gómez, del Centro Médico Nacional La Raza, y del IMSS, en la Ciudad de México. Resultados: Se evaluaron 271 muestras de sangre en tarjetas Guthrie y 271 muestras de saliva para la presencia de CMV. El 3.69% de éstas, resultó positivo al cultivo de saliva, el 4.05% positivas en n-PCR en tarjetas Guthrie, 4.05% positivas para PCR-TR en tarjetas de Guthrie y 1.10% positivas para n-PCR en saliva. La sensibilidad (S) de n-PCR y PCR-TR en tarjetas Guthrie fue de 100%, la especificidad (E) 99%, el valor predictivo positivo (VPP) de 90% y valor predictivo negativo (VPN) 100%. En la n-PCR en saliva, S del 30%, E del 99%, VPP del 75% y VPN del 97%. Ninguno presentó infección sintomática. Los genotipos en los pacientes trasplantados con medula ósea fueron: gB1, 9/30 (30%); gB2, 8/30 (27%); gB3, 4/30 (13%), y gB4, 1/30 (3%); se encontraron genotipos mezclados en 8/30 pacientes (27%). Conclusiones: La sensibilidad en PCR o PCR-TR de las tarjetas Guthrie fue de 100%. No se determinó relación entre la carga viral y sintomatología ya que ningún paciente presentó infección sintomática. Los genotipos predominantes en nuestra población fueron gB2 y gB1. Se encontró una alta proporción de genotipos mezclados.